2012
DOI: 10.1128/jb.00774-12
|View full text |Cite
|
Sign up to set email alerts
|

The β-Lactam Resistance Protein Blr, a Small Membrane Polypeptide, Is a Component of the Escherichia coli Cell Division Machinery

Abstract: In Escherichia coli, cell division is performed by a multimolecular machinery called the divisome, made of 10 essential proteins and more than 20 accessory proteins. Through a bacterial two-hybrid library screen, we identified the E. coli ␤-lactam resistance protein Blr, a short membrane polypeptide of 41 residues, as an interacting partner of the essential cell division protein FtsL. In addition to FtsL, Blr was found to associate with several other divisomal proteins, including FtsI, FtsK, FtsN, FtsQ, FtsW, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 52 publications
0
36
0
Order By: Relevance
“…blr was first identified as a stand-alone gene (40) that, when disrupted, caused increased sensitivity to β-lactam antibiotics (β-lactam resistance) (41) and, surprisingly, decreased sensitivity to cell envelope stress (42). Blr was later identified in a bacterial two-hybrid screen (43) for proteins that interacted with FtsL, an integral membrane protein with a very poorly understood function that is nonetheless a core component of the division machinery (30). The two-hybrid assay also suggested that Blr could associate with other components of the cell division machinery, such as FtsI, FtsK, FtsN, FtsQ, and FtsW (43).…”
Section: Examples Of Small Protein Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…blr was first identified as a stand-alone gene (40) that, when disrupted, caused increased sensitivity to β-lactam antibiotics (β-lactam resistance) (41) and, surprisingly, decreased sensitivity to cell envelope stress (42). Blr was later identified in a bacterial two-hybrid screen (43) for proteins that interacted with FtsL, an integral membrane protein with a very poorly understood function that is nonetheless a core component of the division machinery (30). The two-hybrid assay also suggested that Blr could associate with other components of the cell division machinery, such as FtsI, FtsK, FtsN, FtsQ, and FtsW (43).…”
Section: Examples Of Small Protein Functionmentioning
confidence: 99%
“…Blr was later identified in a bacterial two-hybrid screen (43) for proteins that interacted with FtsL, an integral membrane protein with a very poorly understood function that is nonetheless a core component of the division machinery (30). The two-hybrid assay also suggested that Blr could associate with other components of the cell division machinery, such as FtsI, FtsK, FtsN, FtsQ, and FtsW (43). Consistent with these results, GFP-Blr was found to localize to the division septum of E. coli in a divisome-dependent manner.…”
Section: Examples Of Small Protein Functionmentioning
confidence: 99%
“…Chemically competent E. coli BTH101 cells were co-transformed with 5 ng of plasmids carrying the respective T18 and T25 translational fusion constructs, plated onto LB plates supplemented with 200 µg ml −1 X-gal, 0.5 mM IPTG, Amp, Km and grown at 30°C for 24-36 h. Interactions were quantified by beta-galactosidase assays from three independent colonies. For this aim, cultures were either grown over night at 30 °C or for two days at 20 °C in LB Amp, Km, 0.5 mM IPTG and beta-galactosidase activity was recorded as described in the manufacturer’s instructions (Euromedex; BACTH System Kit Bacterial Adenylate Cyclase Two-Hybrid System Kit) in a 96 well plate according to Karimova, Davi and Ladant 71 .…”
Section: Methodsmentioning
confidence: 99%
“…Beta-galactosidase assays of E. coli BTH101 cells co-expressing indicated T25 and T18 translational fusions of all possible pair-wise combinations. E. coli cells carrying the respective plasmids were subjected to beta-galactosidase assay as described by Karimova et al 71 in triplicates from three independent colonies grown for 2 d at 20 °C. Quantity values are given in Miller Units per milligram LacZ of the mean results from three independent colonies.…”
Section: Supplementary Informationmentioning
confidence: 99%
“…A possible explanation for this observation is that YfgM has several other interaction partners and that binding of these partners may be altered when the N terminus is changed. Most conspicuous in this context is the essential membranebound cell division protein FtsL, which was found as the interaction partner of YfgM in a bacterial two-hybrid screen (83).…”
Section: Toward the Biological Function Of Yfgm-the Function Ofmentioning
confidence: 99%